2011
DOI: 10.1080/09603123.2010.515668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytokine expression in BEAS cells exposed to fine particulate matter (PM2.5) from specialized indoor environments

Abstract: Fine particles were collected in three indoor environments and an outdoor reference site. Samples were acid and aqueous extracted for metal analyses and cytokine expression study using a BEAS-2B line. Results revealed that the average PM2.5 concentration indoors was 5.8 mg/m3 while outside, it was 9.4 mg/m3. The airborne metal concentrations in indoor air ranged from 0.01 ng/m3 (Cd) to 620 ng/m3 (Al). All metals analyzed were higher indoors when compared to outdoor (I/O ratio) indicating a contribution from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
(39 reference statements)
1
19
0
1
Order By: Relevance
“…Urban PM has a strong component of fossil fuel due to concentration of engine emissions and burning in the city as compared to the other sites. It has been well established that, PM 10, PM 2.5 and diesel exhaust particles (DEP) can induce the secretion of inflammatory cytokines and chemokines in epithelial cells and macrophages (Alfaro-Moreno et al, 2007; Becker et al, 2005; Fuentes-Mattei et al, 2010; Gioda et al, 2011b; Hiraiwa and van Eeden, 2013;Ortiz-Martínez et al, 2010; Rodriguez-Cotto et al, 2013; Schwarze et al, 2013). In addition, cytokine induction can be mainly attributed to the effects of heavy metals in PM 2.5 (Rodriguez-Cotto et al, 2013) and residual oil fly ash (Carter et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban PM has a strong component of fossil fuel due to concentration of engine emissions and burning in the city as compared to the other sites. It has been well established that, PM 10, PM 2.5 and diesel exhaust particles (DEP) can induce the secretion of inflammatory cytokines and chemokines in epithelial cells and macrophages (Alfaro-Moreno et al, 2007; Becker et al, 2005; Fuentes-Mattei et al, 2010; Gioda et al, 2011b; Hiraiwa and van Eeden, 2013;Ortiz-Martínez et al, 2010; Rodriguez-Cotto et al, 2013; Schwarze et al, 2013). In addition, cytokine induction can be mainly attributed to the effects of heavy metals in PM 2.5 (Rodriguez-Cotto et al, 2013) and residual oil fly ash (Carter et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Few reports exist on IL-6 or IL-8 inhibition due to PM exposure (Alfaro-Moreno et al, 2007; Alfaro-Moreno et al, 2009; Fuentes-Mattei et al, 2010; Gioda et al, 2011b; Schwarze et al, 2013). It has been reported that exposure to PM could induce (Becker et al, 2005) or inhibit (Veranth et al, 2006) IL-8 cellular secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that PM 2.5 has a potential to stimulate cells to produce and release inflammatory cytokines (Ogino et al 2014). In vitro studies have found that diesel exhaust particles (DEP) and PM increase the expression of granulocyte-macrophage colony-stimulating factor (GM-CSF), tumor necrosis factor-α (TNF-α), interleukin 8 (IL-8), IL-6, IL-1β and eotaxin (C-C motif chemokine ligand 11) in airway epithelial cells (Boland et al 1999;Gioda et al 2011;Patel et al 2011;Tang et al 2012). Since nasal epithelial cells function as the first epithelial barrier in the nasal cavity to protect from inhaled particles, PM 2.5 may induce inflammatory responses in nasal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some evidence which indicates that insoluble metal forms are also capable of causing ROS-mediated damage in the lungs [7], it is widely accepted that soluble metals are likely contributors to the toxic potential of airborne PM [8,9]. The many epidemiological and toxicity studies which have reported an association between various respective cardiorespiratory and toxicological endpoints and the concentration of water soluble metal fractions in airborne PM, most notably Zn, Ni, Cu, V and Fe, support this [e.g., [10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%